Developing inquiry-based lectora multimedia in order to increase the logical ability and the creative thinking - Sumandita Noviani; Muhammad Nur Wangid (Jurnal Prima Edukasia, 2018)
The study aimed at: (1) developing inquiry-based lectora multimedia which is eligible to increase the logical ability and the creative thinking of the fifth-grade students; and (2) measuring the effectiveness of the inquiry-based lectora multimedia development in increasing the logical ability and the creative thinking of the fifth-grade students. The study was a research and development (R D) effort. The developmental design of the study was adopted from the procedures proposed by Borg Gall. In the preliminary field testing, the researcher involved three fifth-grade students from SD Jetis, Bantul. Then, in the main field testing the researcher involved eight fifth-grade students who were not involved in the preliminary field testing. Finally, in the operational field testing the researcher involved 33 students from Grade VA. The product of this study will be an inquiry-based lectora multimedia. Based on the research and development that had been conducted, 117 material experts and 87 learning experts declared that the inquiry-based lectora multimedia development is feasible with “Highly Valid” assessment category. The inquiry-based lectora multimedia development is effective to increase the logical ability and the creative thinking of the fifth-grade students. From the operational field testing, the researcher found that p = 0.003 0.050 and this finding implies that there is an increase in the logical ability and the creative thinking of the fifth-grade students who had been taught using the inquiry-based lectora multimedia in comparison to the students who were not taught using the inquiry-based lectora multimedia.